Alteration of Coagulation Profile in Malaria Patients and its Correlation with The Degree of Parasitemia - Jabeen, Shehneela; Naeem, Samina; Uddin, Nasir; Farooq, Muhammad; Rabbani, Sahar; Basharat, Maria (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the alteration of coagulation profile (PT, APTT, D-dimers) in malaria patients and its correlation with the degree of Parasitemia.Study Design: Cross-sectional study.Place and Duration of Study: Pathology department of Combined Military Hospital Lahore, from Jan to July 2018.Methodology: A total of 92 patients were included in the study. The malarial parasite was identified using thick and thin smears. Hemoglobin, Red blood cell, White blood Count, Prothrombin Time, Activated Partial Thromboplastin Time, and Ddimer levels were measured using automated analyzers Sysmex KX-21 and CA-600. Results: The mean age of the patients was 23.35 ± 14.4 years with 53 (57.6%) males and 39 (42.4%) females. Plasmodium falciparum was identified as the causative species in 33 (35.9%) of the cases, 59 (64.1%) cases were caused by Plasmodium vivax. Based on parasitic load, 50 (54.3%) patients were found to have a mild degree of parasitemia whereas 26 (28.3%) had moderate and 16 (17.4%) had severe parasitemia. A significant association was found between the degree of parasitemia and coagulation parameters.Conclusion: Partial thromboplastin time, activated partial thromboplastin time and D-dimer levels were positively correlated with the degree of parasitemia specifically in plasmodium falciparum as compared to the other species. Therefore, special care should be exercised in patients having an underlying inherited bleeding disorder and a strict prevention protocol should be made.